2010
DOI: 10.1038/nn.2689
|View full text |Cite|
|
Sign up to set email alerts
|

Sortilin associates with Trk receptors to enhance anterograde transport and neurotrophin signaling

Abstract: Binding of target-derived neurotrophins to Trk receptors at nerve terminals are required to stimulate neuronal survival, differentiation, innervation and synaptic plasticity. The distance between the soma and nerve terminal is tremendous, making efficient anterograde Trk transport critical for their synaptic translocation and signaling. The mechanism responsible for this trafficking remains poorly understood. Here we show that the sorting receptor sortilin interacts with TrkA, -B, and –C and enables their ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
162
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 167 publications
(170 citation statements)
references
References 53 publications
6
162
1
1
Order By: Relevance
“…Whether or not this is related to a different ratio of TrkA/p75 NTR between melanoma and breast cancer cells remains to be elucidated, but a common feature between the two models is the necessity of binding to sortilin. A direct interaction between TrkA and sortilin has recently been reported (30), and such an interaction could also occur in breast cancer cells. The fact that neuroten- sin, the natural ligand of sortilin, was found to inhibit the activation of TrkA by proNGF suggests that a direct interaction of proNGF and sortilin is necessary for the stimulation of TrkA.…”
Section: Discussionmentioning
confidence: 94%
“…Whether or not this is related to a different ratio of TrkA/p75 NTR between melanoma and breast cancer cells remains to be elucidated, but a common feature between the two models is the necessity of binding to sortilin. A direct interaction between TrkA and sortilin has recently been reported (30), and such an interaction could also occur in breast cancer cells. The fact that neuroten- sin, the natural ligand of sortilin, was found to inhibit the activation of TrkA by proNGF suggests that a direct interaction of proNGF and sortilin is necessary for the stimulation of TrkA.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have focused on sorting receptors, including VPS10P receptors that bind a range of ligands, from small secretable proteins such as neurotrophic factors (66,67) to large transmembrane proteins including amyloid precursor protein (APP) (68) and Trk receptors (69). For example, sortilin regulates endosomal sorting and lysosomal degradation of brain-derived neurotrophic factors (66,70), as well as anterograde trafficking of TrkB receptors (69,71), while SorLA has been shown to mediate retrograde retention of APP in the trans-Golgi network (68).…”
Section: Discussionmentioning
confidence: 99%
“…For example, sortilin regulates endosomal sorting and lysosomal degradation of brain-derived neurotrophic factors (66,70), as well as anterograde trafficking of TrkB receptors (69,71), while SorLA has been shown to mediate retrograde retention of APP in the trans-Golgi network (68). It has been shown that the ectodomains of VPS10P receptors are responsible for cargo binding (28,66), whereas their intracellular domains dictate the trafficking routes and can vary considerably among different VPS10P family members (72).…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway is composed of the ERK1/2 part, the p38 MAPK part, and the JNK part. Microenvironment communication through neurotrophin signalling could lead to the progression of cancer [157][158][159] while an imbalance in expression of neurotrophin receptors such as sortilin is strongly linked to different types of cancer [160][161][162][163]. In a previous study, we discovered that the EGFR signalling pathways are induced between 3 to 50-fold in endothelial cells exposed to NSCLC exosomes enriched for the neurotensin receptor 3, also known as sortilin [125].…”
Section: Liquid Biopsies-the Future?mentioning
confidence: 99%